First-principles study for physical properties and stability of Li based chalcopyrite semiconductors: Reliable for green energy sources - Kumari, J.; Singh, C.; Choudhary, B.L.; Verma, A.S. (Physics and Chemistry of Solid State, 2022)
In this research study, we have been performed the first principles calculation for physical properties likewise structural, electronic, optical and mechanical properties of the lithium gallium chalcopyrites LiGaX2 (X= S, Se). We have used two exchange correlation potentials one is full potential augmented plane wave method (FP-LAPW) and second is pseudo-potential method. The reported lattice parameters in this work ranging from a = b = 5.28 Å to 5.82 Å and c = 10.11 Å to 11.25 Å and found that these materials have direct band-gap 4.41 eV for LiGaS2 and 2.90 eV for LiGaSe2. Refractive indexes n(ω) is 2.1 and 2.3 respectively for these compounds. The study of optical and elastic properties for these materials ensures that these show the anisotropic behaviour and ductile in nature.